2015
DOI: 10.1101/gr.190629.115
|View full text |Cite
|
Sign up to set email alerts
|

The Mendelian disorders of the epigenetic machinery

Abstract: The Mendelian disorders of the epigenetic machinery are genetic disorders that involve disruption of the various components of the epigenetic machinery (writers, erasers, readers, and remodelers) and are thus expected to have widespread downstream epigenetic consequences. Studying this group may offer a unique opportunity to learn about the role of epigenetics in health and disease. Among these patients, neurological dysfunction and, in particular, intellectual disability appears to be a common phenotype; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
176
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(182 citation statements)
references
References 65 publications
3
176
0
3
Order By: Relevance
“…The most frequent clinical manifestations thereof are intellectual disability, disorders of the neuronal migration, immune dysfunction, growth impairment, and skeletal anomalies. Craniosynostosis is a consistent, albeit rare feature in 4 out of 44 mendelian disorders of the epigenetic machinery [Bjornsson, 2015]. Conceivably, the phenotypic outcome in individual patients may reflect not only disruption of the compartments of the epigenetic machinery, but also the molecular constitution of the target genes [Paro, 1995;Law et al, 2010].…”
Section: Genotype-phenotype Relationshipsmentioning
confidence: 99%
“…The most frequent clinical manifestations thereof are intellectual disability, disorders of the neuronal migration, immune dysfunction, growth impairment, and skeletal anomalies. Craniosynostosis is a consistent, albeit rare feature in 4 out of 44 mendelian disorders of the epigenetic machinery [Bjornsson, 2015]. Conceivably, the phenotypic outcome in individual patients may reflect not only disruption of the compartments of the epigenetic machinery, but also the molecular constitution of the target genes [Paro, 1995;Law et al, 2010].…”
Section: Genotype-phenotype Relationshipsmentioning
confidence: 99%
“…It has been identified that there is a high mutational load in chromatin-modifying genes in developmental disorders [25]. These monogenic disorders strongly indicate the importance of chromatin dynamics and the associated phenotypes commonly including significant behavioural and intellectual disabilities [26]. It is also of note that these genes have also been observed as somatic hotspots in cancers [27].…”
Section: Chromatin Modificationsmentioning
confidence: 98%
“…Mutations in epigenetic enzymes are frequently observed in cancer [42], intellectual disability [43], neurological disorders such as Alzheimer’s, Parkinson’s, and Huntington’s disease [44], and autoimmune diseases such as rheumatoid arthritis [4547] and type 1 diabetes [48]. Most studies have been performed in cancer: ~30% of all driver genes characterized in cancer are related to chromatin structure and function [42].…”
Section: Main Textmentioning
confidence: 99%